Case Report: Apremilast for Therapy-Resistant Pemphigus Vulgaris - Meier, Katharina; Holstein, Julia; Solimani, Farzan; Waschke, Jens; Ghoreschi, Kamran (Frontiers in Immunology, 2020)
Background. In Pemphigus, elucidating the disease-causing immune mechanism and the development of new therapeutic strategies are needed. In this context, the second messenger 3´,5´-cyclic adenosine monophosphate (cAMP) is gaining attention. cAMP is important in hematological and auto-inflammatory disorders. A class of enzymes called phosphodiesterases (PDEs) control intracellular cAMP levels. In pemphigus, cAMP levels increase following IgG binding to Dsg3. This appears to be a mechanism to preserve epithelial integrity. Objectives. To determine whether apremilast, an inhibitor of the PDE4 normally used in psoriasis, may be of benefit in the blistering skin disorder pemphigus. Methods. Here we report of a 62 years old patient with chronic debilitating and recalcitrant pemphigus not responding to several previous treatments, who received treatment with apremilast over a period of 32 weeks. Desmoglein autoantibody levels were assessed by Enzyme-linked Immunosorbent Assay (ELISA), whereas disease severity and quality of life were assessed by the Autoimmune Bullous Skin Disorder Intensity Score (ABSIS). In attempt to explain the effects of apremilast in pemphigus, peripheral blood mononuclear cells (PBMC) were analyzed for the duration of treatment by flow cytometry for the distribution of specialized T cell subsets. The frequencies of circulating T helper (Th) 1, Th2, Th17, Th17.1 and T follicular helper (Tfh) 1, Tfh2, Tfh17 and Tfh17.1 were analyzed by CCR6, CXCR3 and CXCR5 expression of CD4+ t cells. Further, based on the different expression of CXCR5, CD127 and CD25, we analyzed the T regulatory (Treg) and T follicular regulatory (Tfreg) compartment. Results. In response to apremilast treatment, Dsg-specific autoantibody titers decreased, blistering ceased and lesions healed, showing a long-lasting effect. While the frequencies of most of the Th and Tfh cell subsets remained unchanged, we observed a continuous increase in Treg and Tfr cell levels. Conclusion. Our findings are encouraging and warrant extension of the beneficial effect of PDE4 inhibition on a larger cohort of pemphigus patients.